Preparatory attentional templates in prefrontal and sensory cortex encode target-associated information - Zhou, Zhiheng; Geng, Joy (eLife, 2025)
Visual search relies on the ability to use information about the target in working memory to guide attention and make target-match decisions. The ‘attentional’ or ‘target’ template is thought to be encoded within an inferior frontal junction (IFJ)-visual attentional network. While this template typically contains veridical target features, behavioral studies have shown that target-associated information, such as statistically co-occurring object pairs, can also guide attention. However, preparatory activation of associated information within the IFJ-visual attentional network has never been demonstrated. We used fMRI and multivariate pattern analysis to test if target-associated information is explicitly represented in advance of visual search. Participants learned four face-scene category pairings and then completed a cued visual search task for a face. Face information was decoded in the fusiform face area, superior parietal lobule, and dorsolateral prefrontal cortex during the cue period, but was absent during the delay period. In contrast, associated scene information was decoded in the ventrolateral prefrontal cortex during the cue period, and most importantly, in the IFJ and the parahippocampal place area during the delay period. These results are a novel demonstration of how target-associated information from memory can supplant the veridical target in the brain’s ‘target template’ in anticipation of difficult visual search.
Keywords: visual search; target template; associative learning; visual working memory; attentional network